User Acceptance of the SpeedCash Digital Wallet Using TAM - Laura Naily Tsabita; Dwi Fatrianto Suyatno (Universitas Negeri Surabaya, 2026)
The rapid development of financial technology has increased the use of digital wallets as a practical and efficient payment method. One of the developing digital wallet applications in Indonesia is SpeedCash. This study aims to analyze user acceptance of the SpeedCash digital wallet application using the Technology Acceptance Model (TAM). The variables used in this study include perceived ease of use, perceived usefulness, attitude toward using, and behavioral intention to use. This research employed a quantitative approach by distributing questionnaires to SpeedCash users. The collected data were analyzed using the Structural Equation Modeling-Partial Least Square (SEM-PLS) method. The results indicate that perceived ease of use has a positive effect on perceived usefulness and attitude toward using. In addition, perceived usefulness significantly influences users’ attitudes toward using the application. The variable attitude toward using also has a significant effect on behavioral intention to use the SpeedCash application. These findings indicate that ease of use and perceived benefits are the main factors influencing user acceptance of the SpeedCash digital wallet. This study is expected to provide insights for application developers in improving service quality and user experience to increase sustainable application usage.